مكانة أصول الفقه في التأمين الشرعي: دراسة التأمين الشرعي لمستقبل الأطفال من أكسا مانديري الشريعة - Hasbi, Rusli (Al-Zahra : Journal for Islamic and Arabic Studies, 2023)
Amid the many choices of conventional insurance products that are echoed by the private sector and the government, such as health insurance, education, employment, and old age insurance. Besides conventional insurance options, there are also Sharia insurance options. One of the interesting sharia insurance products is sharia child future insurance by AXA Mandiri Syariah. The purpose of this study is to see Maslahah Mursalah in the use of this insurance. This paper will present the position of ushul fiqh in Islamic insurance, a study on the Islamic future insurance program for children by AXA Mandiri Syariah. The analysis used to see this is a literature study related to the literature of the ushul fiqh school. The results of this study indicate that the benefits of using Islamic future insurance are more than not using it. Using the sharia insurance system adds value to the program so that both insurance managers and insurance participants benefit from the program.